Peran Organizational Well-Being terhadap Job Involvement pada Karyawan Produksi PT. XYZ - Sahda Febi Wilendari; Maya Rosmayati Ardiwinata; Nurul Yanuarti (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
The increasing demand for vaccines in Indonesia makes PT. XYZ has high demands for providing vaccines. This makes the performance of the production department being the main key in responding to these needs. Job involvement has a large impact on employee performance. This study aims to see whether there is an influence of organizational well-being on job involvement in the production employees of PT. XYZ. Respondents in this study were 217 production employees at PT. XYZ (209 men, 18 women) aged 26-56 years with a service period of 3-35 years. These results indicate that organizational well-being has significant influence on job involvement of PT. XYZ (p = 0,000; R = 0.557; R2 = 0.310). These results also indicate that organizational well-being has an influence of 31% on job involvement, while the remaining 69% is influenced by other variables not examined in this study.